Marketing for SMEs - Gilmore, Audrey (Henry Stewart Talks, 2012)
Definition of SMEs, SME owner/managers, entrepreneurs, Marketing for SMEs, Adapting standard marketing frameworks for SMEs, Successful SME product focus, SME pricing issues, Cash flow, SME delivery & distribution, SME selling & promotion, SME customer service, SMEs use of e-technology, E-marketing activities & challenges, Using networks, Marketing by networking, Influences on networking, Marketing management competencies for SMEs, Experiential learning and competency development, Innovative marketing in SMEs
Archived at 2022/04/26